2020
DOI: 10.1021/acsnano.0c00324
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Superwettable Microspine Chips with Directional Droplet Transportation for Biosensing

Abstract: Directional droplet transportation without extra energy input remains a challenge in microfluidic biochips for clinical detections. Herein, inspired by the water-collecting behaviors on the cactus spine, we fabricate nanomaterial-based superwettable microspine (SMS) chips. The bioinspired SMS chips are capable of spontaneous and directional droplet transportation by synergistically combining geometric asymmetry and surface superhydrophilicity. Based on theoretical models, the gradient of the Laplace pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 44 publications
0
66
0
1
Order By: Relevance
“…For instance, in the open-channel microfluidic system for diagnosis, which requires droplet transportation, many natural behaviors or properties such as Nepenthes alata, spider silk, shorebird beak, and cactus spine have engendered ideas for droplet transportation, leading to different approaches that apply a different gradient of surface energy or the asymmetrical design of the substrate that can drive the droplet (Wu et al, 2019). Chen et al utilized the behavior of the cactus spine that was capable of directional droplet transportation and fabricated superwettable microspine (SMS) chips with an asymmetrical geometric design, including microchannel and microwell with a superhydrophilic property on the superhydrophobic surface (Gong X. et al, 2020;Guan et al, 2020;Han et al, 2020;Wei D. et al, 2020), which allowed directional droplet transportation by both geometric shape and superhydrophilic property (Figure 4A) (Chen et al, 2020). To better understand the transportation behavior of water droplets, different geometric gradients were measured by the optical contact angle measuring instrument, which revealed that FIGURE 4 | (A) Directional droplet transportation on the superwettable microspine (SMS) chip inspired by the cactus spine.…”
Section: Animal/plant-inspired Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the open-channel microfluidic system for diagnosis, which requires droplet transportation, many natural behaviors or properties such as Nepenthes alata, spider silk, shorebird beak, and cactus spine have engendered ideas for droplet transportation, leading to different approaches that apply a different gradient of surface energy or the asymmetrical design of the substrate that can drive the droplet (Wu et al, 2019). Chen et al utilized the behavior of the cactus spine that was capable of directional droplet transportation and fabricated superwettable microspine (SMS) chips with an asymmetrical geometric design, including microchannel and microwell with a superhydrophilic property on the superhydrophobic surface (Gong X. et al, 2020;Guan et al, 2020;Han et al, 2020;Wei D. et al, 2020), which allowed directional droplet transportation by both geometric shape and superhydrophilic property (Figure 4A) (Chen et al, 2020). To better understand the transportation behavior of water droplets, different geometric gradients were measured by the optical contact angle measuring instrument, which revealed that FIGURE 4 | (A) Directional droplet transportation on the superwettable microspine (SMS) chip inspired by the cactus spine.…”
Section: Animal/plant-inspired Systemsmentioning
confidence: 99%
“…Sensitivity of the SMS chip with increasing concentration of PSA. Specificity examination of the SMS by setting various conditions, including PSA, PSA+CEA+HAS, HAS, carcinoembryonic antigen (CEA), and negative control (Chen et al, 2020). (B) A schematic of fabrication of the SA-DTP, biotin-linker DNA, AS1411 aptamer, and catalytic hairpin assembled (CHA) probes were connected by streptavidin.…”
Section: Animal/plant-inspired Systemsmentioning
confidence: 99%
“…Except for the well‐known fog harvesting, the beetle‐inspired patterned wettable surfaces have been also used for biosensing 88‐91 . The microdroplets can be well anchored on (super)hydrophilic points in small regions.…”
Section: Bioinspired Superwetting Surfaces For Biosensingmentioning
confidence: 99%
“…Superwettability, such as superhydrophobic, superhydrophilic, and tunable wettability has attracted increasing attention in recent years for their applications in self‐cleaning, anti‐fogging, anti‐icing, and so on. [ 1–5 ] To construct efficient superwettability surfaces, various approaches have been developed, including plasma treatment, layer‐by‐layer method, vapor deposition, etc. [ 6–13 ] In recent years, more attention has been paid to films with Janus wettability which have two faces with different properties.…”
Section: Introductionmentioning
confidence: 99%